Smart Phone Based Monitoring of Agricultural Activities - Jiahua Fang (Computational Algorithms and Numerical Dimensions)
This review also looks at the various environmental characteristics that can be used to achieve precision agriculture, such as irrigation, monitoring, soil qualities, and temp, Furthermore, a thorough investigation is carried out on various crops that are covered by WSN technology. The numerous communication technologies and sensors available for PA are also highlighted in this review. Several research questions were developed to examine the influence of WSNs in the agricultural area, and we attempted to discover answers to these research questions through this revised. Compared to the being IoT grounded husbandry and husbandry results, the propose result reduces network quiescence up to a certain extent. In this, a cross sub caste grounded channel access and routing answer for looking and actuating is proposed. We dissect the network structure grounded on content range, and quiescence. In the process of improving GDP of the country agriculture is the main part.